Aerodynamic configuration parametrization and optimization of high-speed gliding vehicle - Deng, Yuehang; Xu, Shangcheng; Wang, Yi (Journal of physics. Conference series, 2025)
According to various mission objectives, the geometric shape of a high-speed gliding vehicle (HGV) is typically subject to significant constraints. To satisfy the stringent design requirements, this paper selects characteristic curves to establish geometric constraints and employs the curve lofting method to derive the vehicle’s aerodynamic shape. The influence of design parameters on the aerodynamic performance and volumetric characteristics of the HGV is examined from the perspectives of performance analysis and flow field analysis, utilizing the control variable method to adjust the cone tip offset. The results indicate that as the cone tip offset increases, the maximum lift-to-drag ratio initially increases and then decreases, while both the volume and volumetric efficiency decline. Additionally, the optimal angle of attack varies by 40%, with the cone tip offset within the range of [0, 200] mm, while the corresponding maximum lift-to-drag ratio varies by only 2%. Subsequently, a parametric sensitivity analysis is conducted on the design variables, comparing the effects of different design variables on the lift-to-drag ratio and the vehicle’s volume. Finally, a multi-objective optimization of the HGV is conducted with the aim of enhancing both the lift-to-drag ratio and volume. The optimization results are analyzed to provide design references for improving the vehicle’s performance.